2018
DOI: 10.1042/bsr20180351
|View full text |Cite|
|
Sign up to set email alerts
|

Adenovirus-mediated small interfering RNA targeting ezrin induces apoptosis and inhibits metastasis of human osteosarcoma MG-63 cells

Abstract: Osteosarcoma is a disease prone to recurrence and metastasis, and adenovirus expression vector is frequently studied as a therapeutic target of osteosarcoma in recent years. The present study attempts to explore the effect of adenovirus-mediated siRNA targetting ezrin on the proliferation, migration, invasion, and apoptosis of human osteosarcoma MG-63 cells. Human osteosarcoma MG-63 cell line was selected for construction of recombinant adenovirus vector. The mRNA and protein levels of ezrin, Bcl2-associated X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In a recent meta‐analysis , the results showed that ezrin expression was not correlated with the distant metastasis of either gastric or esophageal cancers. Ezrin was suggested to be involved in the metastasis of osteosarcoma , and the underlying molecular mechanism involved in the modulation of metastasis by ezrin might be different in different cancers. Previous studies showed that a significant change in ezrin expression was correlated with tumor responses to chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta‐analysis , the results showed that ezrin expression was not correlated with the distant metastasis of either gastric or esophageal cancers. Ezrin was suggested to be involved in the metastasis of osteosarcoma , and the underlying molecular mechanism involved in the modulation of metastasis by ezrin might be different in different cancers. Previous studies showed that a significant change in ezrin expression was correlated with tumor responses to chemotherapy .…”
Section: Discussionmentioning
confidence: 99%